2015
DOI: 10.1021/acs.organomet.5b00814
|View full text |Cite
|
Sign up to set email alerts
|

η5–η1 Switch in Divalent Phosphaytterbocene Complexes with Neutral Iminophosphoranyl Pincer Ligands: Solid-State Structures and Solution NMR 1JYb–P Coupling Constants

Abstract: This paper reports the synthesis of a series of complexes based on the bis­(pentamethylcyclopentadienyl)­ytterbium­(II) (1; Cp*2Yb) and bis­(tetramethylphospholyl)­ytterbium­(II) (2; Tmp2Yb) fragments bearing an additional neutral bis­(methyliminophosphoranyl)­pyridine ligand (L) on which the steric demand is modulated at the phosphorus position (triethyl, L Et ; triphenyl, L Ph ; tricyclohexyl, L Cy ) to yield the original complexes Cp*2YbL Et (1-L Et ), Cp*2YbL Ph (1-L Ph ), Tmp2YbL Et (2-L Et ),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 62 publications
3
16
1
Order By: Relevance
“…The Cp*−Yb average distances in 3 and 4 are similar (2.305(8) and 2.29(1) Å, respectively) and are indicative of the oxidation state of the Yb center. Typical values of 2.30−2.31 Å are observed for Yb III ,18g whereas longer Cp*−Yb distances (2.43−2.50 Å) are indicative of Yb II complexes 20. They oscillate between these limiting values when the electronic ground state is multiconfigurational 18a,b.…”
mentioning
confidence: 99%
“…The Cp*−Yb average distances in 3 and 4 are similar (2.305(8) and 2.29(1) Å, respectively) and are indicative of the oxidation state of the Yb center. Typical values of 2.30−2.31 Å are observed for Yb III ,18g whereas longer Cp*−Yb distances (2.43−2.50 Å) are indicative of Yb II complexes 20. They oscillate between these limiting values when the electronic ground state is multiconfigurational 18a,b.…”
mentioning
confidence: 99%
“…In 2012, Labouille et al. showed that [Sm(Tmp) 2 ] reacted with pyridine to give the adduct [Sm(η 5 ‐Tmp) 2 (py) 2 ] ( 15‐Sm ); [28] the corresponding Yb II complex 15‐Yb was reported in 2015 by Nocton, Auffrant and Cheisson, together with the structures of several similar substituted Yb II bis‐phospholyl complexes coordinated by substituted pyridines, [Yb(Tmp) 2 (L R )] (L R =C 5 H 3 N(CH 2 NPR 3 ) 2 ‐2,6; R=Et, 16 ; Cy, 17 ; Ph, 18 ) [29] (Figure 7). As both [Tm(Cp ttt ) 2 ] [27] and [Sm(Cp*) 2 ] [28] reductively couple pyridine, the lack of SET chemistry of 11 and [Sm(Tmp) 2 ] towards this substrate showcases how the weaker π‐donor properties of phospholyl ligands versus Cp R makes metal centres less reducing.…”
Section: Lanthanide Monophospholyl and ‐Arsolyl Complexesmentioning
confidence: 94%
“…The solid‐state structures of 15‐Ln for both Sm [28] and Yb [29] reveal bent metallocene‐type motifs, with two eclipsed η 5 ‐Tmp ligands with staggered C 4 P rings (Sm−P: 3.043(1) and 3.046(1) Å; Yb−P: 2.903(8) and 2.941(2) Å) and two equatorially coordinated pyridine molecules. The structures of 16 – 18 differ according to the identity of L R , with 16 and 17 containing κ 3 ‐coordinated L R ligands to enforce one η 1 ‐bound Tmp (Yb−P: 2.9723(8) Å for 16 and 3.023(1) Å for 17 ) and one η 5 ‐Tmp (Yb−P: 3.027(1) Å for 16 and 2.925(1) Å for 17 ) [29] . Only one of the iminophosphoranyl arms are bound in the κ 2 ‐L Ph ligand of 18 , thus both Tmp ligands are able to bind in an η 5 ‐fashion (Yb−P: 2.9480(8) and 2.947(1) Å).…”
Section: Lanthanide Monophospholyl and ‐Arsolyl Complexesmentioning
confidence: 99%
“…The P=N bond is also longer than in L Ph H (1.580(1) vs 1.567(1) Å) as already observed for iminophosphoranes featuring alkyl groups on the phosphorus. 6…”
Section: Scheme 1 Synthesis Of L R Hmentioning
confidence: 99%
“…Bochmann and coworkers reported in 2000 the coordination of bis(iminophosphoranyl)pyridine derivatives (A) to iron, cobalt, and nickel centers and used those complexes for olefin polymerization. 5 More recently we studied the coordination of the more flexible ligands B to lanthanides 6 or electron-rich Cu I centers. 7 The ligand C, exhibiting a central anionic pyrrole in place of a pyridine, was employed by the group of Hayes to stabilize rare earth complexes 8 or prepare Rh I complexes able to promote CO activation in presence of borane.…”
Section: Introductionmentioning
confidence: 99%